Earnings management in Malaysian companies during the global financial crisis and the coincidental effect of IFRS adoption - Ayedh, Abdullah Mohamed; Fatima, Abdul Hamid; Mohamad, Muslim Har Sani (University of Wollongong, 2019)
Purpose: This research examines earnings management (EM) behavior during the 2008 financial crisis in Malaysia. Both magnitude and direction of EM are studied and compared with EM during the pre-crisis period. In the case of Malaysia, the Malaysian Accounting Standards Board (MASB) adopted the international accounting standards, i.e. the International Financial Reporting Standards (IFRS) just two years prior to the crisis period. These standards could have some influence on EM during the global financial crisis period in Malaysia, thus are also taken into consideration in this study.